2018
DOI: 10.1002/jsfa.9028
|View full text |Cite
|
Sign up to set email alerts
|

Rapid prediction of deoxynivalenol contamination in wheat bran by MOS‐based electronic nose and characterization of the relevant pattern of volatile compounds

Abstract: These results indicate that the e-nose method could be a useful tool for high-throughput screening of DON-contaminated wheat bran samples for their classification as acceptable / rejectable at contamination levels close to the EU maximum limit for DON, reducing the number of samples to be analyzed with a confirmatory method. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Pyrazine, methyl-, which was negatively associated with preference in the present study, was positively associated with the level of the mycotoxin deoxynivalenol (DON) in con-taminated barley grain [29]. Similarly, Lippolis et al [34] found that hexanal, 1-pentanol and 1-octen-3-ol were positively correlated with DON concentrations measured in contaminated wheat bran. A higher level of nonanal was also detected in samples with the mycotoxin Ochratoxin A, even at Ochratoxin A concentrations less than 5 µg/kg [29].…”
Section: Discussionsupporting
confidence: 64%
“…Pyrazine, methyl-, which was negatively associated with preference in the present study, was positively associated with the level of the mycotoxin deoxynivalenol (DON) in con-taminated barley grain [29]. Similarly, Lippolis et al [34] found that hexanal, 1-pentanol and 1-octen-3-ol were positively correlated with DON concentrations measured in contaminated wheat bran. A higher level of nonanal was also detected in samples with the mycotoxin Ochratoxin A, even at Ochratoxin A concentrations less than 5 µg/kg [29].…”
Section: Discussionsupporting
confidence: 64%
“…The growth and biochemical pattern of mycotoxigenic fungi species cause chemical changes in the VOCs’ composition and a correlation between VOCs and mycotoxin concentration in food can be observed [ 150 ]. The e-nose has been successfully used for detection of OTA in dry-cured meat [ 151 ], AFs and fumonisins in maize [ 150 ] and DON in wheat bran [ 152 ] and in durum wheat [ 153 ]. In order to achieve wide usage of e-nose in the detection of mycotoxins, optimization for the quantification of low levels of mycotoxins in food samples is necessary.…”
Section: Techniques Used In Detection and Analysis Of Mycotoxinsmentioning
confidence: 99%
“…Several studies have already considered the use of mVOCs as potential biomarkers to detect the presence of fungi [48] and even mycotoxin contamination [49].…”
Section: Potential Mvocs Markersmentioning
confidence: 99%